Attention, Interest, Search, Action, and Share (AISAS) Analysis of Promotion Effectiveness of Zomato - Putri Utami Ruswandi; Hartoyo Hartoyo; Mukhamad Najib (Binus Business Review, 2021)
Current technological advances, especially the Internet of Things (IoT), are widely used by people in their daily lives to transact, communicate, and find various information. The research analyzed the effectiveness of promotions carried out by companies based on the concept of marketing communication from technological developments, namely the Attention, Interest, Search, Action, and Share (AISAS) model, and how to increase consumer purchases. The research applied a descriptive approach by distributing questionnaires to Zomato Gold members, with a sample size of 180 people. Data analysis applied Structural Equation Modeling (SEM) to see the relationship between promotion, attention, interest, search, action, and share variables. The finding shows that the effectiveness of promotional advertising based on the AISAS model is not significant enough to encourage consumers to make purchases by visiting restaurants with Zomato Gold benefits. Therefore, Zomato needs to increase promotional activities on social media to increase consumers’ attention regarding these promotions by maximizing social media features. The increase in consumers’ attention to promotions will increase their opportunities to be interested, seek information, make purchases, and share information and experiences with others. However, when consumers pay attention to a promotion, they are not immediately interested in the advertisement. So, it is necessary to study other factors, such as internal factors that affect consumers, apart from external factors that influence consumers’ interest and purchasing decisions.